Geothermal System of the Dieng-Batur Volcanic Complex - M.T. Zen (Journal of Mathematical and Fundamental Sciences, 1971)
This paper is mainly concerned with the evaluation of reports on geophysical and geochemical surveys made by Group Seven Inc. and Truesdell in the Dieng Mountains under contract with US-AID and on behalf of the Directorate General for Power and Electricity and the Indonesian Geological Survey and partly also with the author's own field observation on geothermy in the Dieng Mountains in Central Java. All the accumulated data lead to the conclusion that the geothermal system of eastern Dieng originated through the intersection of two major fracture zones. The high chloride content found in various streams gives good reason to accept that the geothermal system of the Dieng Mountains is a system of hot water and steam rather than a system of dry steam only. The hot springs in the Dieng Mountains might represent surface manifestation of a deep, neutral, hot water "reservoir". The distribution of geo-electric anomaly which resulted from two dipole mapping surveys delineated a belt of anomalously low resistivity in the eastern Dieng Mountains in which there are three areas of very low resistivity indicating systems of up-welling thermal water. These systems might be connected at great depth. The area with low resistivity anomaly might indicate a reservoir having a volume of 5 to 6 cubic kilometers at depth of 2 kilometers. An estimate based on geophysical data suggests that a power production rate of 200 megawatts could be supported for 25 years, or of 100 megawatts for 50 years. Based on all those data an exploratory deep drilling work is recommended which is due to start in June 1971.